Integrating Pecha Kucha presentations into agile methodologies - Aragonés-Jericó, Cristina; Canales-Ronda, Pedro (Journal of Management and Business Education, 2023)
The main objective of this article is to explain the educational experience of the Pecha Kucha Day event in the subject Financial Marketing, and its integration into the teaching-learning process of agile methodologies. The experience is developed within the framework of an educational innovation project that is based on the implementation and development of innovative active methodologies for teaching-learning in marketing, applied to real business scenarios and placing the student body at the center. To analyze the results, an exploratory quantitative and descriptive analysis of the feedback provided to the 28 Pecha Kucha exhibitions held at the event has been carried out. Likewise, at the end of the subject, a student survey was carried out, reaching a sample of 91 students, out of a total of 115 people enrolled in the subject. Most Pecha Kucha exhibitions are visual, have coherent and well-defined content and an appropriate exhibition style. Student evaluations show that agile education has a very positive influence on their commitment, their satisfaction, and the development of soft skills.